Stigma Surrounding Sexually Transmitted Infections among Medical Students in Germany. Issue 1 (2nd January 2021) - Klein, Verena; Brunner, Franziska; Grabowski, Max; Turner, Daniel
ABSTRACT: Stigmatization by health care professionals leads to decreased help-seeking behaviors in those being stigmatized. Prejudicial attitudes are especially pronounced concerning sexually transmitted infections (STIs), which is crucial in light of rising prevalence rates of STIs in recent years. We aimed to examine stigmatization against patients with sexually versus non-sexually transmitted infections among medical students in Germany. We also assessed how a person's sexual orientation or gender might contribute to stigma. Medical students (N = 332) read about a fictious patient with symptoms of pharyngitis after having had a casual sex encounter. Gender (female/male) and sexual orientation (hetero-/bi-/homosexual) of the patient as well as the pathogen causing the infection (gonococcus/H1N1-virus) were randomly varied. Afterwards, stigma against the patient was assessed. Patients with a gonococcal pharyngitis were perceived as more prone to engage in risky behavior, dumber, and less responsible than patients with a H1N1-virus pharyngitis. Bisexual patients were perceived as more prone to engage in risky behavior than hetero- and homosexual individuals. The predictability of the consequences of the patient's actions was rated higher in bisexual patients. Stigmatizing attitudes toward patients with a STI were frequent, especially against bisexual patients. More education should be dedicated to sexual/LGB health during medical school to reduce existing stigma.